Effects of biodiesel fuel temperature on performance and emissions of a compression ignition (CI) engine - Mustaffa, Norrizal (2013)
Diesel engines are still widely needed and applicable to light duty passenger car and heavy duty vehicles. In recent years, limited supply of fossil fuel makes alternative sources of fuel especially biodiesel receiving a lot of attention in the automotive industry. However, in using biodiesel as fuel had created poor fuel-air mixing that generally will produce lower performance and higher emissions than diesel fuel. This is associated with the fuel properties especially viscosity that higher compared to diesel fuel. The aim of this present research was to investigate the effects of C on performance and emissions of diesel engine at three different load conditions, which are 0% load, 50% load and 100% load. A four-cylinder four strokes cycle, water cooled, direct injection engine was used for the experiments. The results showed that the maximum performance produced was at 0% load condition with the 60 preheated biodiesel based crude palm oil (B5, B10 and B15) at 40 o o o C, 50 C and 60 o C of heating temperature by B10 where the torque, flywheel torque and brake power increased by 11.55%, 11.42% and 4.16% respectively compared to diesel fuel. While for the emissions, the preheat temperature results on the decrement of CO emission for all load conditions and the maximum reduction recorded was 41.2%. However, the increment of fuel temperature promotes to the higher NOx emissions produced and the maximum increment recorded was 51.7%.